Penerapan Alat Peraga Pohon Bilangan untuk Meningkatkan Kemampuan Motorik dan Sensorik pada Anak Usia Dini - Jihan Hidayah Putri; Israq Maharani; Putri Elmania (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The introduction of number tree learning media in early childhood is an activity that utilizes number tree media in order to introduce the concept of numbers to early childhood. The aim of using this learning media is to introduce the concept of numbers based on children's understanding of the numbers 1-10 by showing the numbers in the numbers, asking children to order the numbers 1-10 and then join in attaching the correct order to the number tree. This number tree learning media can help children introduce the concept of numbers 1-10 with an attractive appearance. The development aspects that are easily seen are the motor and sensory development aspects. Aspects of motor development are easy to see because they are related to children's physical activity. Sensory ability is a process that refers to the child's brain's ability to receive, interpret, or reason and use information obtained through the five senses, which is characterized by the activity of showing, repeating what has been seen and heard. The sensory and motor development of each individual is not the same, this can be caused by genetic and environmental factors. This research was conducted by RA- Islam Nur Medan on Monday 31 July 2023. The activity in carrying out this service was the use of number trees to introduce numbers and addition to develop students' motor and sensory abilities. By paying attention to children's motor and sensory development, parents and teachers can help to develop children's motor and sensory development by providing media that supports children's development while playing where children are fully involved in play activities, besides that teachers can design thematic-based activities and utilize media as a tools to facilitate activities and physical activities carried out.